GIS-material for the archaeological project: The Målaren block and others - The "Målaren" block and others - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
The Swedish National Heritage Board's contract archaeology division, UV Öst, has performed a stage 2 survey, due to local planning within the Målaren block and others, in the city and parish of Skänninge, Mjölby municipality. Three distinct and nine uncertain features were found within the 110 000 m2 big area. UV Öst suggests no further archaeological measures.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the survey was to investigate whether the affected area contained any archaeological remains.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har utfört en arkeologisk utredning etapp 2 inför detaljplanearbete inom Kvarteret Målaren m.fl., Skänninge stad och socken, Mjölby kommun. Inom den ca 110 000 m2 stora ytan påträffades tre säkra och nio osäkra anläggningar. UV Öst föreslår inga ytterligare arkeologiska åtgärder.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska utredningen var att avgöra om fast fornlämning finns i det aktuella området.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Kvarteret Målaren m fl
Keywords: stone age; stenålder; Bronze Age; bronsålder; Iron Age; järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi